The role of PDGF-B/PDGFR-BETA axis in the normal development and carcinogenesis of the breast. (November 2018) - Jitariu, Adriana-Andreea; Raica, Marius; Cîmpean, Anca Maria; Suciu, Silviu Cristian
Abstract: PDGFs/PDGFRs axis is documented as an important tumor-promoting agent and potential therapeutic target for several human carcinomas, including breast cancer. However, little is known about the role played by the PDGF family members in the normal development of the breast tissue, breast carcinogenesis and tumor-microenvironment dynamics Despite its potent pro-lymphangiogenic effects, PDGF-B/PDGFR-beta axis remains controversial and incompletely elucidated in the field of breast cancer, with emphasis to its differential implications in breast cancer molecular subtypes. Although some data are available concerning this aspect, little or no information is found regarding the role of the PDGF-B/PDGFR-beta axis in rare and aggressive types of breast cancers, such as triple negative breast cancers (TNBCs) and its associated subtypes This review attempted to gather as many data as possible concerning PDGFs family members in the normal breast tissue and in breast carcinogenesis with special focus on their role in diagnosis and therapeutic approach.